Pengaruh Brand Experince dan Brand Image terhadap Loyalitas Pengunjung di Hotel Truntum Padang - Pina Ulandari; Rian Surenda (Lembaga Pengembangan Kinerja Dosen, 2024)
This research begins with the discovery of problems related to guests being less satisfied in terms of facilities and services at Truntum Hotel Padang. The purpose of this study was to analyze the effect of Brand Experience and Brand Image on Visitor Loyalty at Hotel Truntum Padang. The research population was 3890 guests of Truntum Padang Hotel with purposive sampling method obtained a sample of 97 respondents. Data analysis was carried out with descriptive statistical tests and SPSS.16. The results of the study were seen from the average respondents on the brand experience variable 90.46% with very good criteria, the brand image variable 89.86% with very good criteria, and the visitor loyalty variable 94.41% with very good criteria. The results of multiple linear regression tests obtained an F count value of 15.618 with a sig of 0.00 <0.05, so regression can be used. Brand experience and brand image have a significant effect on visitor loyalty. The adjusted R square value of 0.233 means that the brand experience and brand image variables affect 23.3% of the Truntum Padang Hotel.